Analisis Faktor-Faktor Yang Mempengaruhi Self Disclosure Oleh Pengguna Facebook Dengan Menggunakan Structural Equation Modeling (SEM) - Aniela Cahya Ningroem; Ari Kusyanti; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Social media is a web based on internet that facilitate all users can communicate, participate, mutual sharing and forming an online network and disseminate their own content. Facebook is social network service that can invited friends to the number of active users by 47 % . With the number of users who upload personal information on facebook users can publish their personal information on facebook and has several factors. The purpose of this study reseach can find factors that affect the users in publish self disclosure on facebook. Accoding to factors analysis that used in this research is Structural Equation Modeling (SEM). In this research there are seven variable latent is Perceived Control, Trust in Povider, Trust in Member, Risk, Habit, Self Disclosure, and Benefit.So in the SEM analysis there are three stages steps that should be tested is Confirmatory Factor Analiysis (CFA) with Measurement model, Overall model fit and Struktural model fit with Path analysis. So the result of this research is the factors that affect users in self-publish through personal information upload self personal information with trust in member between benefit with self discosure, perceived control with perceived control with trust in providers, trust in provider by risk and perceived control with trust in member.